Upaya Meningkatkan Persepsi dan Hasil Belajar Kimia Siswa Kelas XII IPA 2 SMA Negeri 5 Cilegon Tp 2014/2015 Pada Konsep Sifat Koligatif Larutan melalui Pembelajaran Kontekstual - Nasrullah (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2016)
Student perception has an important role in learning in school. Students are said to have a good perception of these students are able to master and understand and interpret a subject matter taught by the teacher in class. To strengthen students' perceptions, teachers must work on certain learning strategies that are appropriate to the subject matter being taught. Contextual learning is a learning strategy that emphasizes the process of full student involvement to be able to find the material being learned and relate it to real-life situations so that it encourages students to be able to apply it in their lives. The low student learning outcomes in chemistry subjects can result in less than optimal teaching and learning processes so that the subject matter presented becomes incomplete. The condition of students of class XII IPA 2 SMA Negeri 5 Cilegon TP. 2014/2015 totaled 32 students were relatively heterogeneous. The purpose of this CAR is: To improve the perceptions and learning outcomes of students of class XII IPA 2 SMA Negeri 5 Cilegon TP 2014/2015 on the concept of the colligative nature of solutions through contextual learning. PTK Conclusion: Chemistry learning for students of class XII IPA 2 in SMA Negeri 5 Cilegon TP. 2014/2015 through contextual learning can improve perceptions and learning outcomes from cycle to cycle. PTK recommendation: Contextual learning can be applied by chemistry teachers in other schools because it will improve students' perceptions and learning outcomes in chemistry subjects.